Question
upstudy study bank question image url

Resolve \( \frac{1-x-x^{2}}{(1-x)\left(1-x^{3}\right)} \) into partial fractions.

Ask by Peterson Williams. in Nigeria
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\[ \frac{2}{3(1 - x)} - \frac{1}{3(1 - x)^2} + \frac{2x + 2}{3(1 + x + x^{2})} \]

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

The Deep Dive

To resolve the expression \( \frac{1-x-x^{2}}{(1-x)(1-x^{3})} \) into partial fractions, we start by factoring the denominator. The factor \( 1 - x^3 \) can be factored using the identity \( a^3 - b^3 = (a - b)(a^2 + ab + b^2) \). Thus, we can write: \[ 1 - x^3 = (1 - x)(1 + x + x^2). \] The complete factored form of the denominator is: \[ (1-x)(1-x^3) = (1-x)(1-x)(1+x+x^2) = (1-x)^2(1+x+x^2). \] Now we can set up the partial fraction decomposition: \[ \frac{1-x-x^{2}}{(1-x)^{2}(1+x+x^{2})} = \frac{A}{1-x} + \frac{B}{(1-x)^{2}} + \frac{Cx + D}{1+x+x^{2}}. \] Now, we multiply both sides by the denominator \( (1-x)^{2}(1+x+x^{2}) \) to eliminate the denominator: \[ 1 - x - x^2 = A(1-x)(1+x+x^2) + B(1+x+x^2) + (Cx+D)(1-x)^2. \] Next, we need to expand the right-hand side and collect like terms: 1. Expand \( A(1-x)(1+x+x^2) \): \[ A(1 - x + x + x^2 - x^2) = A(1 - x^2). \] 2. Expand \( B(1+x+x^2) \): \[ B + Bx + Bx^2. \] 3. Expand \( (Cx + D)(1-x)^2 \): \[ (Cx + D)(1 - 2x + x^2) = (Cx + D)(1 - 2x + x^2) = Cx - 2Cx^2 + Cx^3 + D - 2Dx + Dx^2. \] Combining all parts gives us: \[ 1 - x - x^2 = (A+D) + (B - 2D - C)x + (B + C - 2A)x^2 + Cx^3. \] Now we equate coefficients for \( x^0, x^1, x^2, x^3 \): 1. For \( x^0 \): \( 1 = A + D \) 2. For \( x^1 \): \( -1 = B - 2D - C \) 3. For \( x^2 \): \( -1 = B + C - 2A \) 4. For \( x^3 \): The coefficient is \( 0 = C \). Setting \( C = 0 \) in the equations, we can simplify: From \( C = 0 \): \\ The equation for \( x^0 \): \( 1 = A + D \) → \( D = 1 - A \). \\ The equation for \( x^1 \): \( -1 = B - 2(1 - A) \) → \( B + 2A = 1 \). \\ The equation for \( x^2 \): \( -1 = B - 2A \). Now substituting \( D = 1 - A \) into the second equation \( B + 2A = 1 \): Rearranging gives \( B = 1 - 2A \), and substituting this back into the last equation: \[ -1 = (1 - 2A) - 2A, \] which simplifies to \( -1 = 1 - 4A \) leading to: \[ 4A = 2 \implies A = \frac{1}{2}. \] So from \( D = 1 - A = \frac{1}{2} \) and substituting \( A = \frac{1}{2} \) into \( B + 2(1/2) = 1 \): \[ B + 1 = 1 \implies B = 0. \] In summary, we have: \[ A = \frac{1}{2}, B = 0, C = 0, D = \frac{1}{2}. \] Thus, the partial fraction decomposition is: \[ \frac{1-x-x^{2}}{(1-x)^{2}(1+x+x^{2

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy